Effect of uptake of improved seed potato and donor-funded training on smallholder farmers’ market participation - Kangogo, E.; Otieno, David Jakinda; Okello, J.J.; Mwenye, O.; Kapalasa, E. (Wiley, 2024)
Enhancing the productivity of crops through the adoption and uptake of technologies improves farmers' socio-economic status through increased market participation. However, smallholder farmers in Sub-Saharan Africa (SSA) face a myriad of challenges that make it difficult for them to access and participate in the output markets. Like most SSA countries, the uptake of improved technologies is still low in Malawi. This paper examines the relationship between uptake of improved potato seed and donor-funded training on market participation. Using secondary data from 393 potato farmers in Malawi, the study applied a triple-hurdle model to examine the extent to which such interventions and other socio-economic and institutional factors influence market participation. The results showed that male-headed farm households, more experienced farmers, and those who participated in CIP-led training were likely to market their potato output. Further, farmers closer to urban centers, those with off-farm income, those who had participated in potato training, use of improved potato seed and quantity of output positively influenced the decision to sell in high-value markets such as supermarkets. On the other hand, land size, ownership of transport equipment, group membership, and access to credit had positive effects on the amount of potato sold while distance to the markets reduced the quantity sold. Based on these findings, there is a need to set up a seed system within the local communities where farmers can easily access the seeds. Additionally, there is a need for a collaborative effort between public and private sector stakeholders to invest in the production of improved potato seeds that would help to address the shortfall in supply. Finally, institutional support interventions that utilize farmer groups as a key entry point in sustaining training on improved potato seed, relaxing credit constraints and promoting diversification into off-farm enterprises would enhance potato production and marketing.